The Extent of Religious and Spiritual Determination in Resilience and Coping Ability Among University Students Amidst Pandemic - Nur Alim (Institut Agama Islam Negeri Kendari, 2022)
This study explored two main issues, (1) the extent of resilience in academic achievement among university students amidst Covid-19 socio-economic restriction policies, and (2) the map of the students' coping abilities to deal with uncertain situations. An 8-item Academic Success Inventory indicated academic achievement for College Students (ASICS) scale, the resilience level was measured by the 25-item Connor-Davidson Resilience Scale (CDRS) and the coping abilities were mapped using the 21-item Coping Inventory for Stressful Situations (CISC-21). The focus group discussion (FGD) and peer interviews were later used to confirm the results of the scales. 263 respondents passed the inclusion criteria with different demographic backgrounds, including affiliations, economic status, and study assistance. The results dictated that according to 8-item ASICS scale, the mean score was 3,81 which means impressive. Concerning the resilience level, 25-item CDRS unveiled the mean score of 4,08 which means highly resilient. The 21-item CISC noted 3,8 of the mean score, which means good. Regarding the mapping of respondents' coping abilities, emotion-oriented coping category was more dominant. This study suggests the need for a special task force to locate, list, and facilitate students who struggled to meet academic and economic demands due to the global pandemic.